2015
DOI: 10.1136/neurintsurg-2015-011909
|View full text |Cite
|
Sign up to set email alerts
|

In vitro experiments of cerebral blood flow during aspiration thrombectomy: potential effects on cerebral perfusion pressure and collateral flow

Abstract: Background: Mechanical thrombectomy with stenttriever devices is associated with significantly better outcomes than thrombolysis alone in the treatment of acute ischaemic stroke. Thrombus aspiration achieves high patency rates, but clinical outcomes are variable. The aim of this study was to examine the effect of different suction conditions on perfusate flow during aspiration thrombectomy. Results:The mathematical model predicted that in a patent vessel perfusate is drawn from upstream of the catheter tip, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…The flow restriction created by the ANCD is also restricted to the affected artery, minimizing the hemispheric flow arrest created by the use of a BGC positioned and inflated in the ICA. In addition, it is reasonable to assume that the power of aspiration will increase if the occluding catheter is positioned just proximal to the clot since there are in that case no large side branches between the catheter and the clot 24. When aspiration is performed from a BGC in the ICA, the aspiration force in the MCA may be lessened as it is shared with large branches such as the anterior cerebral artery or the posterior communicating artery.…”
Section: Discussionmentioning
confidence: 99%
“…The flow restriction created by the ANCD is also restricted to the affected artery, minimizing the hemispheric flow arrest created by the use of a BGC positioned and inflated in the ICA. In addition, it is reasonable to assume that the power of aspiration will increase if the occluding catheter is positioned just proximal to the clot since there are in that case no large side branches between the catheter and the clot 24. When aspiration is performed from a BGC in the ICA, the aspiration force in the MCA may be lessened as it is shared with large branches such as the anterior cerebral artery or the posterior communicating artery.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the dependent variable in these studies was flow, not suction force, which, as previously mentioned, does not accurately represent the action of catheter on clot. Computational flow and In vitro analyses have shown that aspiration forces are effective only if the catheter tip is in direct contact with the thrombus 11…”
Section: Discussionmentioning
confidence: 99%
“…There is a variety of access catheters, ranging from small (5F-7F) guiding catheters to large-bore sheath catheters (8F) and BGCs, but there is no consensus about which access catheter is most suitable. 4,8,[11][12][13] Mechanical thrombectomy is becoming more common, and many interventionalists must decide which technique to choose. Because empiric data are lacking and large randomized prospective studies are needed to resolve this issue from a clinical point of view, we addressed this question with a simple technical approach.…”
mentioning
confidence: 99%